DEMOCRATIC EXPERIENCES AND PRACTICES IN KENYA (1992-2013): A CRITICAL ASSESSMENT - Juma, Wamalwa; Cletus, Chukwu N.; Mary, Wahome N. (IJRDO - Journal of Social Science and Humanities Research, 2018)
The years of 1960s and 70s, Kenya was often portrayed as one the few successful democracies in Africa. Compared to other African states, Kenya exhibited some democratic achievements by the occurrence of regular competitive elections, and in 1978, a peaceful transfer of power. This, however, was short lived as Murungi (1992) observed that a few years later, President Daniel Arap Moi discarded the subtle façade of democracy and openly altered the democratic institutions and processes of political participation in Kenya.  Among such changes was the introduction of queue system of voting, change of constitution among others.  Thus, Kenya which had started as a young democracy at independence, instead of improving, deteriorated to a point when people started to call for democracy. This paper examines democratic practices and experiences in the contemporary Kenya between 1992 and 2013.  The examination is based on the democratic ideals which include, but not limited to, freedom to form and join organizations, be they political parties, social movements, or civic, professional and welfare associations;  freedom of expression and movements; universal adult suffrage; eligibility, in principle, of any citizen to seek public office; right of political leaders to compete freely for support and votes; free, fair and competitive elections; accountable governmental decision-making institutions; and freedom of elected officials from overriding opposition emanating from unelected officials.